Fetal Ascites Secondary to In Utero Perforation of Ileal Atresia. A case report - Silva , Hermann (2026)
Meconium peritonitis (MP) is a sterile inflammatory process that causes ascites by chemical reaction of meconium following the perforation of an intestinal atresia. We present the case of a newborn with PM due to perforation of an intrauterine ileal atresia. He had a history of polyhydramnios and fetal ascites. Surgery on the ninth day revealed ileal perforation, mesentery defect, abundant fibrin, and entero-enteric and entero-peritoneal adhesions; an ileostomy was performed. The patient evolved satisfactorily and gained weight by 3 months.